Condensation quasi-local heat transfer and frictional pressure drop of R1234ze(E) and R134a in a micro-structured plate heat exchanger. (October 2021) - Wang, Ru; Kabelac, Stephan
Highlights: Experimental thermohydraulic results for condensation of R1234ze(E) and R134a. Mixed 27°/63° plates with microstructure are used. Analysis of condensation mechanisms and influencing factors. Comparison between empirical correlations in literature and experimental data. New heat transfer and pressure drop correlations are developed. Abstract: Plate heat exchangers with an enhanced surface are attracting continuous attention as a smart option to acquire a more efficient heat transfer performance. Despite of a large number of research dedicated to the two-phase heat transfer, the understanding of condensation heat transfer mechanisms is still defective. In this paper, the experimental results of the quasi-local heat transfer coefficient and the two-phase frictional pressure drop during condensation of R1234ze(E) and R134a are reported in a micro-structured plate heat exchanger with mixed plates showing a chevron angle of 27°/63° and a hydraulic diameter of 5.5 mm. The measurements were carried out with 110 groups of data for pure R1234ze(E) and 163 groups of data for pure R134a respectively. The mass flux and saturation temperature range from 34.08 to 70.64 kg/m 2 s, 22.51 to 40.84 °C (corresponding to p sat  = 4.62–7.84 bar, p r  = 0.13–0.22) for R1234ze(E), and 46.39 to 77.9 kg/m 2 s, 24.93 to 38.03 °C ( p sat  = 6.64–9.64 bar, p r  = 0.16 – 0.24) for R134a. The effect of mass flux and saturation pressure is discussed, the experimental results indicate that the condensation in the micro-structured plate heat exchanger is shear-controlled, the transition from partial film flow to full film flow occurs at  x  ≈ 0.35–0.45. The characteristics of the two-phase frictional pressure drop for the mixed 27°/63° plates is similar to soft plates. Based on existing correlations, the experimental results are compared with predictive results by existing empirical correlations, and new correlations with better accuracies are developed by taking the influence of different parameters into consideration.